Exploring the scientific and technological achievement transformation policies in Chinese universities: based on policy text analysis and PMC-index model - Liu, Shuming; Li, Youbao; Ma, Hongxia; Guan, Lili (Frontiers in Education, 2025)
The transformation of scientific and technological achievements in universities urgently needs to be implemented. To assess the effectiveness of scientific and technological achievement transformation policies in Chinese universities, this study develops an evaluation system using the PMC-index model. This study quantitatively evaluates 10 key policies on the transformation of scientific and technological achievements in Chinese universities based on PMC-index values and PMC-surface analysis. The results show that the PMC-index scores of the selected 10 policies range from 3.85 to 7.99, with an overall upward trend. The average PMC index score for the 10 policies was 6.21. Of the policies, five were rated as excellent in terms of consistency, four were rated as acceptable, and one was rated as low. This study further analyzes the overall effectiveness, primary variables, and PMC-surface results for the policy samples. The findings suggest that China's current university scientific and technological transformation policies perform well in four areas: policy content, policy evaluation, policy implementation agencies, and policy functions. However, there is still a need for adjustments and optimizations in terms of policy issuing agencies, policy implications, and policy safeguards. And countermeasures and suggestions are proposed from three aspects: joint departmental release, establishment of a conversion platform, and establishment of an incentive mechanism. This study helps identify the strengths and weaknesses of scientific and technological transformation policies, providing a foundation for developing future policies in Chinese universities.